Application of the Fure Method in Studying Wave Propagation During the Movement of a Fluid in a Damper Pipe (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
An analytical solution to the linearized problem describing the propagation of pressure and fluid velocity disturbances in an inclined section of a pipeline with an air cap is obtained taking into account the gravitational effect, friction forces, and a local inertial component. The effect of the air cap is modeled based on I.A. Charny's approach. The initial equations formulated based on N.E. Zhukovsky's theory are solved using the method of separating variables in the presence of mixed boundary conditions. Based on the obtained solution, numerical modeling is performed, which makes it possible to identify the nature of changes in hydrodynamic disturbances depending on a number of factors, including the volume of the air cap.